Sexual and Reproductive Health in Nursing Undergraduate Program Curriculums in Turkey: A Cross-sectional Study - Fatma Uslu Şahan; Sevda Yıldırım Hamurcu (Galenos Publishing House, 2023)
Objective:Nursing students must learn to provide holistic care, including sexual and reproductive health (SRH), during their education to provide adequate and quality care to healthy/patient individuals. This study aimed to examine the characteristics of SHR courses in nursing undergraduate program curricula in Turkey.Method:The descriptive and cross-sectional study's population consisted of 154 undergraduate nursing programs affiliated to state and private universities in Turkey. The sample consisted of 95 undergraduate nursing programs with SRH courses in their curriculum. The data were collected by screening the course contents from the web pages of undergraduate nursing programs.Results:In Turkey, 61.69% of 154 universities with undergraduate nursing programs have SRH courses. SRH courses are offered under different names in undergraduate nursing programs; 94.6% are elective and primarily offered in the fourth (24.1%) and fifth (24.1%) semesters. The evaluation methods for all courses included a final exam, and most learning methods were homework/self-study (60%). 93.5% of the courses had two national credits, 36.6% had three European Credit Transfer System credits, and 94.7% had two theoretical hours. In the study, there are 27 topics grouped under the titles of "sexual health", "reproductive health", and "SRH" in the SRH course content, most of which are of medium prevalence.Conclusion:SRH courses are not sufficiently included in Turkey's undergraduate nursing programs curriculum. The SRH courses should be integrated into undergraduate nursing programs, and standardization should be ensured in the course content throughout the country.